Caliber-persistent labial artery: report of 3 cases - José Antonio Llamas Carmona; Ángela Rivera Mercado; Miguel Lova Navarro; Elisabeth Gómez Moyano (Sociedade Brasileira de Dermatologia, 2022)
Abstract The caliber-persistent labial artery is a vascular anomaly in which a primary arterial branch penetrates into the submucosal tissue without reduction in diameter. Most lesions are benign and do not require treatment, except for complications and/or on patient demands. In this way, noninvasive diagnostic tools are preferred such as high-resolution and color Doppler ultrasonography which allow direct observation of the lesion, assessing its exact location and diameter at every axis, as well as the blood flow velocity. An excisional biopsy of these lesions or even their surgical extirpation could have a fatal outcome with profuse bleeding.